Formation of Different Isomers of Phosphine–Imidazolyl and –Pyridyl Ruthenium(II) Complexes Affecting the Catalyst Activity in the Acceptorless Dehydrogenation of Alcohols. Issue 4 (19th January 2015) - Langer, Robert; Gese, Alexander; Gesevičius, Donatas; Jost, Maximilian; Langer, Bastian R.; Schneck, Felix; Venker, Alexander; Xu, Weiqin
Abstract: The synthesis, reactivity, and catalytic activity of Ru II complexes with different pyridine‐ and imidazole‐based P, N ligands are reported. The investigations reveal a strong influence of the N‐heterocycle and the steric demand of the phosphine groups on the stability of different isomers of [L2 RuX2 ] (L = P, N ligand; X = Cl, H). The imidazole‐based complex5 with dicyclohexylphosphine groups was found to be the most active precatalyst for the acceptorless dehydrogenation of primary alcohols, whereas different phosphine groups at the imidazole ligand as well as pyridine‐based ligands caused a drop in catalytic activity. In the presence of a primary amine, imines are preferentially formed under these conditions. In summary, the investigations show that comparably small changes in the ligand moiety have a strong effect on the relative stability of stereoisomers for both hydride and chloride complexes, whereas isomerization of the kinetic reaction products was observed in some cases. The described changes in the ligand moiety most probably have a strong impact on the relative stabilities of isomeric intermediates as well and thus affect the catalytic activity of these complexes. Abstract : Different ruthenium dichloride complexes with P, N ligands have been synthesized and compared in their activity in the acceptorless dehydrogenation of primary alcohols, thereby demonstrating that small changes in the ligand moiety have a strong impact on the relative stability of isomeric dihydride and dichloride complexes and thus on the catalytic activity.